(untitled) (Research, Society and Development, 2021)
The purpose of the study carried out was to determine the relationship of the strategic actions and digital teaching materials implemented by the facilitators or teachers on the learning of students aged 3 to 6 with intellectual disabilities in the city of Azogues. In this case, the study approach was quantitative and Pearson’s correlational descriptive type, while the applied design was non-experimental, transectional. We worked with a population composed of 12 students with intellectual disabilities, considering the application of the observation sheet, for which two formats of questions were designed aimed at evaluating each of the variables studied. The results of the Pearson correlation demonstrated that teaching strategies and materials (DME) are favorably related in an order of 0.639 with learning in children with intellectual disabilities (ADI); in which case the correlation was found to be significant at the bilateral 0.05 level. However, based on the discussion carried out, it was determined that the digital teaching materials and strategies used should be applied more efficiently to obtain better results at the learning level, mainly in the case of students with a higher degree of intellectual disability since according to research they show greater learning difficulties.